(untitled) (Research, Society and Development, 2021)
Creatine is an organic compound, an amine, not an amino acid, and is an organic substance extracted from meat. Creatine has been much researched due to its potential effect on the physical performance of athletes involved in high intensity and short duration, intermittent exercises with short recovery periods (Corrêa; Lopes, 2014). Creatine can be produced by our body as it is made from non-essential amino acids. However, it is common to see people who practice weight training using creatine supplementation to increase performance in training and gain muscle mass (Medeiros et al., 2010).A bibliographic survey was carried out in order to characterize and analyze available information and published studies on the subject. Searched through REDALYC, LYLACS, MEDLINE, and SCIELO: atleta/athletes, creatina/creatine, creatinina, hipertrofia, muscular strength, muscle power, saudável/healthy.